Simultaneous determination of gelsemine and koumine in rat plasma by UPLC‐MS/MS and application to pharmacokinetic study after oral administration of Gelsemium elegans Benth extract. (2nd March 2018) - Wang, Lin; Wen, Yanqing; Meng, Fanhao
Abstract: A simple, rapid and sensitive method using UPLC‐MS/MS was established and validated for simultaneous determination of gelsemine and koumine in rat plasma after oral administration of Gelsemium elegans Benth extract. Plasma was performed with methanol precipitation and berberine was chosen as the internal standard. Plasma samples were separated on an Acquity UPLC® BEH C18 column (3.0 × 50 mm, 1.7 μm) with gradient elution using acetonitrile and 0.1% formic acid aqueous solution as the mobile phase at a flow rate of 0.4 mL/min. Multiple reaction monitoring mode in positive ion mode was utilized for detection. The calibration curves were linear over the range of 0.2–100 ng/mL for gelsemine and 0.1–50 ng/mL for koumine, with the lower limits of quantification 0.2 and 0.1 ng/mL, respectively. The intra‐ and inter‐precision and accuracy were well within the acceptable ranges. The developed method was successfully applied to an in vivo pharmacokinetic study in rat after oral administration of 10 mg/kg Gelsemium elegans Benth extract.